Hypertension Efek Bisoprolol Terhadap Penurunan Tekanan Arteri Rata-rata dan Laju jantung Pada Tikus Putih Jantan Hipertensi Dan Hipertensi komplikasi Hiperkolesterolemia: Hipertensi,Hiperkolesterolemia,Arteri rata-rata,Hiperkolesterolemia,Bisoprolol - Miming Andika (LPPM Universitas Abdurrab, 2022)
Hypertension is a cardiovascular disease that often occurs in Indonesia. This is a health problem with a high prevalence, which is 25.8%, according to the 2013 Riskesdas data. People with hypertension also often experience complications with other cardiovascular diseases such as hypercholesterolemia. Beta-blockers are commonly used by people to treat high blood pressure and an excessive heart rate. Experiments on the pharmacological effect of bisoprolol on reducing blood pressure in hypertensive conditions have been carried out by several previous researchers, both preclinically and clinically, but the effect of pathological hypercholesterolemia on the effect of decreasing mean arterial pressure and heart rate has not been established. Therefore, researchers are interested in investigating the effect of decreasing mean arterial pressure and heart rate in hypertensive and hypertensive rats with comorbid hypercholesterolemia. So researchers are interested in conducting research on the effect of bisoprolol on decreasing mean arterial pressure and heart rate in hypertensive male white rats and hypertension complicating hypercholesterolemia in male white rats. In this study, all experimental animals were hypertensive first, then the group with complications of hypercholesterolemia was induced by PTU and high fat diet, then measured using a photometer v5Â¬+ 5010. Meanwhile, the mean arterial pressure and heart rate were measured using a blood pressure gauge adinstrument NIBP ( Non invasive blood pressure) brand CODA (kent scientific). The data from this study were analyzed by two-way ANOVA. It was found that the administration of bisoprolol with doses of 2.5 mg, 5 mg and 10 mg significantly decreased mean arterial pressure and heart rate (p 0.05). And the 10 mg dose was the most effective in reducing the mean arterial pressure and heart rate in hypertensive male white rats and hypertension complicating hypercholesterolemia. And there is a difference in the decrease in mean arterial pressure and heart rate in male white rats with hypertension, the decrease is greater than in male white rats with hypertension complicated by hypercholesterolemia.